A Review of Anti-hyperglycemic Effects of Curry Leaf Tree (Murraya koenigii) - Vinotha Sanmugarajah; Gowri Rajkumar (Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Diabetes mellitus is becoming a metabolic disease defined by the level of hyperglycemia. Nowadays, it has a serious threat to public health throughout the world. Constituents and extracts isolated from diverse natural resources, mainly plants, have been a rich store for controlling and treating diabetes problems. Numbers of research are ongoing to identify suitable traditional medical drugs, medicinal herbs, and resources for managing this condition. Murraya koenigii Spreng (Family Rutaceae) is commonly known as a 'curry leaf tree' locally. It is widely scattered in India and Sri Lanka, and leaves are widely used for cooking purposes and also primarily used for various health conditions such as diabetes, anemia, and diarrhea. The present review was to aim to do critical thinking on the anti-hyperglycemic effect of the curry leaf tree based on the review, in vitro, in vivo, and clinical studies. Based on this review, the M. koenigii possess flavonoids, phenols, saponins, alkaloids, tannins, and cardiac glycosides. It has shown a potential anti-hyperglycemic effect on induced diabetic rats. This review reported the potential of curry leaf and its extract to be a high-value dietary product in terms of its anti-hyperglycemic results and its industrial profits. Therefore, the present review supports the researchers and readers/users to realize the importance of using the curry leaf tree in the management of diabetes mellitus. Further, this review provides valuable documents for future scientific-related clinical trials in diabetic patients.